Trials of Local Microorganism Composition (Mol) Toward Growth and Production Plant Lettuce (Lactuca Sativa) - Erwin Pane; Marwan Marwazi (Budapest International Research and Critics University, 2020)
Experiments of Various Local Microogranism Composition (MOL) Against Growth and Production of Lettuce (Lactuca sativa). This study aims to determine the effect of giving various MOLs to the growth and production of lettuce (Lactuca sativa). The design used in this study was a Non Factorial Randomized Block Design (RBD) with MOL composition treatment factors, consisting of 4 levels of treatment, namely: M0 = control, M1 = ¼ kg papaya + ar palm sugar + 2 L coconut water + 2 L rice washing water, M2 = ¼ kg papaya + ¼ palm sugar + 2 L coconut water + 2 L rice washing water + ¼ kg bamboo shoots, and M3 = ¼ kg papaya + ¼ palm sugar + 2 L coconut water + 2 L water rice washing + ¼ kg of maja fruit, and repeated 6 times. The parameters observed in this study were plant height, number of leaves, root length and wet weight of the harvest. The results showed that the treatment of various MOL compositions did not significantly affect the growth and production of lettuce plants.